Modified Deterministic Modelling For Tuberculosis Infection - Sulayman, Fatima (2024)
Tuberculosis (TB), caused by the Mycobacterium tuberculosis, is one of the contagious disease that mainly attacks human lungs and caused 10.6 million new infection globally, with an average of 1.6 million people dying. In general, mathematical modelling can serve to understand the transmission pattern and identify suitable controls in preventing the infections. Through mathematical modelling as well, the dynamics of an infection can be predicted more effectively. This in turn leads to the main purpose of this thesis where four compartmental deterministic models for tuberculosis infection is proposed. The developed models addressed the important factors related to the transmission of tuberculosis infection, such as public health education and hospital treatment, an imperfect vaccine, nonlinear saturated recovery (treatment) and optimal control.